2020
DOI: 10.1088/2058-6272/ab9ddd
|View full text |Cite
|
Sign up to set email alerts
|

Applications of atmospheric pressure plasma in microbial inactivation and cancer therapy: a brief review

Abstract: Atmospheric pressure cold plasma, with advantages such as high particle activity, no thermal damage, high efficiency and direct and friendly contact with human tissues, is considered to have great potential in biomedical applications. Therefore, 'plasma medicine' as a new interdiscipline has been developed in the past two decades. This review first briefly describes the development of typical plasma sources suitable for biomedical applications, and those with different discharge forms are simply compared, eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 237 publications
0
22
0
Order By: Relevance
“…The use of cold atmospheric (-pressure) plasmas (CAPs) is increasingly being considered for various biomedical applications such as wound healing and blood coagulation 1 3 , sterilization and bacterial susceptibility 4 7 , treatment of cancer 6 , 8 , and various other pathologies 9 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cold atmospheric (-pressure) plasmas (CAPs) is increasingly being considered for various biomedical applications such as wound healing and blood coagulation 1 3 , sterilization and bacterial susceptibility 4 7 , treatment of cancer 6 , 8 , and various other pathologies 9 11 .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to cancer treatment, various strategies using different types of CAPs have recently shown promising effects in cellular tumor models of breast cancer 12 14 , cervical cancer 13 15 , liver cancer 16 , lung cancer 17 , skin cancer 18 22 , and other cancers 6 , 8 . Numerous therapeutic advantages of CAPs over treatments with conventional chemotherapeutic agents have been identified as a result of previous studies, the most important being probably the selective effect of cold plasma on normal and carcinoma cells 22 24 .…”
Section: Introductionmentioning
confidence: 99%
“…NTP itself works effectively on head and neck squamous cell carcinoma cells [20], and recently, it has been reported that it has a remission effect when applied clinically [21]. Additionally, previous studies have attempted to create a cooperative anticancer effect on cancer cells by combining GNP with NTP [22][23][24]. As a result, it was confirmed that the cell cycle of cancer cells was stopped, and cell death was induced.…”
Section: Introductionmentioning
confidence: 90%
“…Plasma medicine [1] is one of the most widely concerned interdisciplinary fields of cold atmospheric plasmas (CAPs) owing to its great potential in clinical treatment. Up to now, it has been proved that CAPs are efficient in aspects ranging from sterilization [2] and disinfection [3] to wound healing [4,5], skin disease treatment [6], and even cancer therapy [7]. These results show that the CAP treatment can be more effective than the traditional method for certain diseases with few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the CAP sources used in plasma medicine are operated at atmospheric pressure and have gas temperatures close to room temperature, making it feasible and convenient to be applied for the treatment of biological materials such as living tissues, cells, etc. Detailed descriptions and features of various kinds of CAP sources used in plasma medicine can be found in some topical reviews [7,9,10].…”
Section: Introductionmentioning
confidence: 99%